Pengaruh Metode Diskusi Kelompok Terhadap Kemampuan Menulis Teks Persuasif Siswa Kelas VIII SMPN 37 Medan - Hadida Aprilia Munthe; Inayah Hanum Lubis (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
This research aims to describe students’ ability in writing persuasive text before and after using group discussion method in class VIII students of SMPN 37 Medan. The research method used was experimental with one group pretest postest design. The instruments used were pretest and postest written tests. The results showed that before using the group discussion method, students’ ability in writing persuasive texts was still lacking with an average score 59,37. However, after using the group discussion method, students’ abilities improved to good with an average score of 77,73. Data analysis showed a significant effect of group discussion method on students’ persuasive text writing ability. This is evidenced by the result of statistical calculations that show the normality test of pretest and postest data is normally distributed, the homogeneity test states that the sample is homogeneous, and the hypothesis test rejects H0 and accepts Ha. This research implies that the group discussion method is effective in improving students’ persuasive text writing ability in class VIII of SMPN 37 Medan.